Normal birth weight at 3 400 m above sea level - Villamonte Calanche, Wilfredo (2015)
Objectives: To determine the 5th, 10th, 50th, 90th and 95th birth weight percentiles of newborns from normal singleton pregnant women without pathology at 3 400 m above sea level (Cusco). Design: Descriptive and retrospective study. Setting: Adolfo Guevara Velazco National Hospital, EsSalud, Cusco, Peru. Participants: Newborns. Interventions: Birth weight analysis of 8 500 normal neonates recorded between 1998 and 2006 in the Perinatal Information System database. Results: Only the 36 through 42 weeks neonates showed appropriate number of cases to be analyzed. We obtained the 5th, 10th, 50th, 90th, and 95th percentiles of newborns birth weights. Conclusions: Male newborns birth weights were higher than female neonates and increased through gestation.